Metagenomic‐based impact study of transgenic grapevine rootstock on its associated virome and soil bacteriome. Issue 1 (9th August 2017) - Hily, Jean‐Michel; Demanèche, Sandrine; Poulicard, Nils; Tannières, Mélanie; Djennane, Samia; Beuve, Monique; Vigne, Emmanuelle; Demangeat, Gérard; Komar, Véronique; Gertz, Claude; Marmonier, Aurélie; Hemmer, Caroline; et al.
Summary: For some crops, the only possible approach to gain a specific trait requires genome modification. The development of virus‐resistant transgenic plants based on the pathogen‐derived resistance strategy has been a success story for over three decades. However, potential risks associated with the technology, such as horizontal gene transfer (HGT) of any part of the transgene to an existing gene pool, have been raised. Here, we report no evidence of any undesirable impacts of genetically modified (GM) grapevine rootstock on its biotic environment. Using state of the art metagenomics, we analysed two compartments in depth, the targeted Grapevine fanleaf virus (GFLV) populations and nontargeted root‐associated microbiota. Our results reveal no statistically significant differences in the genetic diversity of bacteria that can be linked to the GM trait. In addition, no novel virus or bacteria recombinants of biosafety concern can be associated with transgenic grapevine rootstocks cultivated in commercial vineyard soil under greenhouse conditions for over 6 years.